2011
DOI: 10.5005/jp-journals-10006-1147
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Clinical and Neuroimaging Findings affecting Management in Postpartum Eclampsia: A Prospective Study

Abstract: Objectives: To correlate clinical and radiologic findings, to determine whether brain tomography affects management and routinely indicated in uncomplicated postpartum eclampsia and to differentiate it from other potentially treatable conditions. Methodology: This was a prospective hospital-based study of 28 postpartum eclamptics with atypical or complicated course. Neuroimaging was done after stabilizing them with standardized eclampsia regimen. The relationship between maternal demographic, clinical and neur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 9 publications
1
9
0
Order By: Relevance
“…A similar study from Tumkur, Karnataka reported the mean maternal age as 23.89 years (range 18-30 years). 5 In this study, 66% of women had postpartum eclampsia while 34% had antepartum eclampsia. These results were also similar to the epidemiological and interventional studies conducted in the developing countries like Nepal and Zimbabwe.…”
Section: Discussionmentioning
confidence: 54%
See 4 more Smart Citations
“…A similar study from Tumkur, Karnataka reported the mean maternal age as 23.89 years (range 18-30 years). 5 In this study, 66% of women had postpartum eclampsia while 34% had antepartum eclampsia. These results were also similar to the epidemiological and interventional studies conducted in the developing countries like Nepal and Zimbabwe.…”
Section: Discussionmentioning
confidence: 54%
“…28.6% (8) of postpartum seizures were due to CVT. 5 In this study, 52 cases had CT findings. Among these significantly higher number women, i.e.…”
mentioning
confidence: 70%
See 3 more Smart Citations